(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The continuous improvement in the growth rate of urbanization in Indonesia is causing an increased need for work, limited residential land, and high prices for residential development in urban areas. This phenomenon has an impact on the low occupancy rate for the millennial generation and this makes developers offer co-living space which is considered capable of solving the problem of accommodation and its use as a living space is becoming increasingly popular in recent times. Therefore, this study aimed to identify the factors influencing the formation of habitual occupancy among millennials in the co-living space of Indonesia. The process involved using a survey method with online questionnaires to collect data from the study population which consisted of the millennial generation with a sample size of 190 respondents. The data obtained were processed using exploratory multivariant statistics to show the relationship between the latent variables used in forming habitual behavior in shared living. The results showed 10 factors which constitute the living behavior in co-living space and they include public facilities, social, place attachment, feeling of satisfaction, environment, intrinsic, extrinsic, group development, economy, and workspace availability.